The Influence of Mn(II) and Aging Time in the Ferrihydrite to Goethite Transformation - Alvarez, Mariana (2008)
The ferrihydrite-goethite transformation in samples of pure- and Mn-ferrihydrite was investigated in order to elucidate the effect of Mn(II) in the aging process. Samples of pure- and Mn-ferrihydrites were aged for different times, and their structural changes were described on the basis of Rietveld structure refinements. A comparison of two series of samples with (A-series) and without Mn (F-series) shows b- enlargement and a- and c- shortening due to the presence of Mn during the complete aging process. However, with aging different trends are observed in both the series. In the samples synthesized without Mn(II) the variations in all the unit-cell constants are virtually negligible, whereas in the series with Mn(II) more significant changes are reflected by the enlargement of a- and c- and the shortening of the b. These results confirm that the dimensions of the lattice parameters depend not only on the substitution ratio but also on the aging history of the sample.